Kepraktisan dan efektifitas LKPD berbasis think pair share berbantuan video animasi terhadap pemecahan masalah operasi hitung bentuk aljabar siswa SMP - Septi Atika; Della Maulidiya; Effie Efrida Muchlis (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2026)
The low mathematical problem-solving ability in algebraic arithmetic operations and the use of monotonous teaching materials are the background for the need for learning innovation. This study aims to describe the practicality and effectiveness of Student Worksheets (LKPD) based on Think Pair Share (TPS) assisted by animated videos on algebraic arithmetic operations to improve problem-solving skills of seventh-grade students. This research is an Educational Design Research with Development Studies type using the Plomp model. The subjects were 28 students of class VII at SMP Negeri 2 Bengkulu. The instruments used were practicality sheets based on the USE questionnaire and problem-solving ability tests based on Polya's indicators. Practicality data were analyzed using percentages, while effectiveness was analyzed using paired sample t-test and N-Gain calculation. The results showed that the LKPD was practical with teacher practicality percentage of 100% and students’ percentage ranging from 64.28% to 96.43%. The paired sample t-test obtained t = -25.93 (df=27, p<0.001), indicating a significant difference between pretest and posttest scores. The average N-Gain was 0.68 (medium category).